Vaginal Urinary Calculi Formation Secondary to Vaginal Mesh Exposure with Urinary Incontinence - Kara M. Griffiths; Geoffrey D. Towers; Jerome L. Yaklic (Case Reports in Obstetrics and Gynecology)
Background. Vaginal stones may form in the setting of mesh exposure with urinary incontinence. This report serves to help understand the presentation, evaluation, and management of vaginal urinary stones. Case. A 68-year-old female presented with a vaginal calculus. She had a history of anterior and posterior polypropylene mesh placement for prolapse 7 years earlier and urinary incontinence. The stone was identified on a portion of exposed mesh and removed in office. Pathology confirmed urinary etiology. The exposed mesh resolved with topical estrogen. Cystourethroscopy excluded urinary fistula and bladder mesh erosion. Conclusions. When identified, a vaginal calculus should be removed and evaluated for composition. Cystourethroscopy should be performed to assess potential urinary tract fistulas and mesh erosion. Additional imaging should be considered.